The effect of house prices on fertility: Evidence from Canada - Jeremy Clark; Ana M. Ferrer (Kiel Institute for the World Economy (IfW), 2019)
Persistent house price increases are a likely candidate for consideration in fertility decisions. Theoretically, higher housing prices will cause renters to desire fewer additional children, but home owners to desire more children if they already have sufficient housing and low substitution between children and other "goods", and fewer children otherwise. In this paper, the authors combine longitudinal data from the Canadian Survey of Labour Income and Dynamics (SLID) and averaged housing price data from the Canadian Real Estate Association to estimate the effect of housing price on fertility in a housing market that has historically been less volatile and more conservative than its American counterpart. The authors ask whether changes in lagged housing price affect the marginal fertility of homeowner and renter women aged 18-45. They present results both excluding and including those who move outside their initial real estate board area, using initial area housing prices as an instrument in the latter case. For homeowners, they find evidence that lagged housing prices have a positive effect on marginal fertility and possibly on completed fertility, while for renters they find no significant effects.
Keywords: D13; J13; J18; R21; 330; economic determinants of fertility; housing prices; wealth effects; home ownership